Correction: Endurance-trained subjects and sedentary controls increase ventricular contractility and efficiency during exercise: Feasibility of hemodynamics assessed by non-invasive pressure-volume loops - Östenson, Björn; Ostenfeld, Ellen; Edlund, Jonathan; Heiberg, Einar; Arheden, Håkan; Steding-Ehrenborg, Katarina (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0285592.].